2016
DOI: 10.1080/17429145.2016.1267270
|View full text |Cite
|
Sign up to set email alerts
|

Study of interaction effect between triacontanol and nitric oxide on alleviating of oxidative stress arsenic toxicity in coriander seedlings

Abstract: In this study, triacontanol (TRIA) and nitric oxide (NO) interaction on arsenic (As)-induced oxidative stress tolerance in coriander (Coriandrum sativum L.) plants was investigated. The results showed that As had a significant adverse effect on the plant's biomass. The seedlings pretreated with TRIA and NO significantly increased growth reduction induced by the metalloid. The obtained results indicated that the application of TRIA and sodium nitroprusside (SNP) generally reduced oxidative markers such as of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 54 publications
(59 reference statements)
0
7
1
Order By: Relevance
“…The difference between our results and that of Saha et al [77] could stand on species-specific reactions of proline upon metal stress as tobacco under cadmium also did not enhance leaf proline levels even after 25 days of treatment [78]. Phenolic compounds enhance antioxidant enzyme activities and serve as antioxidants themselves [55], probably also due to their readiness to chelate metals [27]. In our study, the phenolic compound contents tended to increase at both As levels in the leaves of both genotypes.…”
Section: Antioxidant Molecules Accumulation Resulting From As Stresscontrasting
confidence: 89%
See 2 more Smart Citations
“…The difference between our results and that of Saha et al [77] could stand on species-specific reactions of proline upon metal stress as tobacco under cadmium also did not enhance leaf proline levels even after 25 days of treatment [78]. Phenolic compounds enhance antioxidant enzyme activities and serve as antioxidants themselves [55], probably also due to their readiness to chelate metals [27]. In our study, the phenolic compound contents tended to increase at both As levels in the leaves of both genotypes.…”
Section: Antioxidant Molecules Accumulation Resulting From As Stresscontrasting
confidence: 89%
“…Anthocyanins are also an important sink of photosynthates, and in SYL, photosynthesis was disturbed at 30 µg l −1 . In Coriandrum, a decrease of antioxidant contents, including anthocyanins, was found under As treatment, therefore Coriandrum is probably a sensitive plant [27]. In tolerant tomato, Kumar et al [84] found increased anthocyanins accompanied by an increase in carotenoids.…”
Section: Antioxidant Molecules Accumulation Resulting From As Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the worst effects of salt toxicity is the overproduction of ROS which alter the cellular redox balance, thus generating oxidative stress ( Del Buono et al, 2020 ). ROS negatively impact on cells ( Asadi Karam et al, 2017 ; Boari et al, 2019 ) and are generated during photosynthesis and respiration because of intense electron flux ( Liang et al, 2018 ). However, they can also act as signals involved in controlling decisive processes related to plant development and growth ( Bulgari et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the mixture, some small molecules, showing biostimulatory effects, positively alert physiological and biochemical processes, including seed germination, root nodulation formation of legume crops, light utilization, crop nutrient absorption, and adverse stresses tolerance [14][15][16][17][18]. Triacontanol promoted growth, photosynthetic capacity [19], and functioned as an antioxidative agent through inhibiting peroxidative damage of cellular proteins and lipids [20]. Brassinolide application improved the drought tolerance in maize through modulation of enzymatic antioxidants and leaf gas exchange [21].…”
Section: Introductionmentioning
confidence: 99%